Pengaruh Pengalihfungsian Lahan Pertanian Menjadi Permukiman Terhadap Sosial Ekonomi Masyarakat (Studi Kasus Lahan Sawah Di Kec. Widodaren, Kab. Ngawi) - Umi Nur Atni Setyaningsih; Nofi Fatmawati; Muhammad Daffa Maulana; Shifa Nur’Afrianti; Hany Nurpratiwi (Universitas 45 Surabaya, 2023)
For human life, land is very important. In its development, land use always develops and triggers land conversion, as happened in Widodaren District, Ngawi Regency. This land conversion occurs due to the sale of crops in cheap markets so that people's economic income decreases and the high population growth causes the need for settlements to increase. Thus the researcher wishes to conduct research related to this matter. This study aims to determine the effect of converting paddy agricultural land into settlements which has an impact on the socio-economic community in Widodaren District, Ngawi Regency. This research uses descriptive research method. In collecting data, this study uses literature, such as previous research reports, news from the internet and other literature. Land conversion is a process of land use that is different from its proper use. In Widodaren District, the use of land for settlements increased from 13.7% to 17.4%, while the use of paddy fields tended to decrease from 49.2% to 43.8%. This is due to the cheap selling price of farmers' crops on the market, high population growth and lack of assistance from the government so that a lot of abandoned agricultural land has an impact on economic growth, namely declining levels of livelihood, the number of human resources and productive activities.